2019
DOI: 10.1111/jfb.14216
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal inheritance of parental rDNAs distribution pattern detected by FISH in diploid F1 hybrid progeny of Cobitis (Teleostei, Cobitidae) species has non‐Mendelian character

Abstract: This study was conducted to describe the major and the minor rDNA chromosome distribution in the spined loach Cobitis taenia (2n = 48) and the Danubian loach Cobitis elongatoides (2n = 50), and their laboratory‐produced diploid reciprocal F1 hybrid progeny. It was tested by fluorescence in situ hybridisation (FISH) whether the number of 28s and 5s rDNA sites in the karyotypes of diploid hybrids corresponds to the expectations resulting from Mendelian ratio and if nucleolar organiser regions (NOR)were inherited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Otherwise, Ag-NORs were very specific for the hybrid, located in two non-homologous chromosomes different in size, allowing an accurate diagnosis of the hybrid. The presence of NORs in chromosomes with distinct morphology have been previously detected for hybrids of Pimelodus (Hashimoto et al 2009) and a similar situation was observed for species of Cobitiis and their hybrids (Grabowska et al 2019). A considerable number of metaphases or nucleolus with only one active NOR indicated dominant rDNA expression of one parental species in the hybrid, fact already described for other hybrid of fishes (Hashimoto et al, 2012;Prado et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Otherwise, Ag-NORs were very specific for the hybrid, located in two non-homologous chromosomes different in size, allowing an accurate diagnosis of the hybrid. The presence of NORs in chromosomes with distinct morphology have been previously detected for hybrids of Pimelodus (Hashimoto et al 2009) and a similar situation was observed for species of Cobitiis and their hybrids (Grabowska et al 2019). A considerable number of metaphases or nucleolus with only one active NOR indicated dominant rDNA expression of one parental species in the hybrid, fact already described for other hybrid of fishes (Hashimoto et al, 2012;Prado et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…We successfully applied our markers on chromosomes of hybrid individuals and found them suitable to unambiguously identify their genomic composition. Earlier, cytological identification of species from this complex comprised only of the description of chromosomal morphology and rDNA markers (5S rDNA, 28S rDNA) [ 19 ]. However, rDNA markers in C. taenia , are highly polymorphic even within different individuals from the same population [ 22 , 81 ], making them an insufficient tool to observe evolutionary traits or unambiguously infer the genomic composition of hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, precise genome and/or ploidy identification relied on a combination of multiple diagnostic approaches: sequencing of multiple mitochondrial and nuclear loci, allozyme, and cytogenetic analyses (e.g., karyotyping and C-banding, rDNA FISH) [ 9 , 18 , 19 ]. However, many important scientific questions regarding the consequences of hybridization, polyploidy, and asexuality on chromosomal and genome evolution require more fine-scale markers allowing the identification of sub-genomes within the nuclei of hybrids.…”
Section: Introductionmentioning
confidence: 99%